The fascination of Islam - Robinson, Neal (Islam and Christian-Muslim relations, 2002)
An Orientalist painting reproduced on the cover of the English translation of Rodinson's La fascination de l'Islam prompts some initial reflections about elements of distortion and projection in European perceptions of the Muslim world. The rest of the article charts the growth of the academic study of Islam and makes some suggestions as to how it might develop in the future. The second section surveys the history of Islamic Studies in Western Europe, dealing in turn with Christian scholarship, text-based Orientalism, and the contribution of the political sciences. It highlights the merits of these approaches but also explains why Muslim students find them problematic. The third section considers a traditional Muslim approach to the subject, as described by Ibn Khaldun. Because of its emphasis on the transmission of information on religious authority, this approach would be inappropriate in a modern Western university. Moreover, as a historian, Ibn Khaldun was already aware of its deficiencies. The fourth section opens by stressing that there is an urgent need to bring Western scholarship and traditional Muslim scholarship into constructive dialogue with each other. Despite the enormity of the task, it would be facilitated if Islamicists of all persuasions were prepared to learn from colleagues in Religious Studies and Theology. With this in mind, a number of suggestions are made as to how Islamic Studies stands to be enriched through contact with these two disciplines. Finally, the author states that Religious Studies and Theology also stand to benefit from the relationship. For example, he suggests that the rise of Islam raises important issues for those who are interested in the formative period of Christian doctrine.